A survey of models for inference of gene regulatory networks - Ristevski, Blagoj (Nonlinear Analysis: Modelling and Control, 2013)
In this article, I present the biological backgrounds of microarray, ChIP-chip and ChIPSeq technologies and the application of computational methods in reverse engineering of gene regulatory networks (GRNs). The most commonly used GRNs models based on Boolean networks, Bayesian networks, relevance networks, differential and difference equations are described. A novel model for integration of prior biological knowledge in the GRNs inference is presented, too. The advantages and disadvantages of the described models are compared. The GRNs validation criteria are depicted. Current trends and further directions for GRNs inference using prior knowledge are given at the end of the paper.
Keywords: gene regulatory networks; gene expression; transcription factors; reverse engineering; GRNs validation